Lécba benigních onemocnĕní hrtanu CO2 laserem - Betka, J; Klozar, J; Kasík, P; Taudy, M; Tichý, S (Sbornik lekarsky, 1989)
CO2 laser surgery is becoming a part of larynx surgery. The authors inform about their experience in benign larynx tumours treatment. They present analysis of concrete therapeutic procedures in individual larynx affections. They conclude that laser surgery is an advantegous method for benign larynx tumours treatment.
Keywords: Laser Therapy; nemoci laryngu; Humans; nádory hrtanu; laserová terapie; Laryngeal Neoplasms; lidé; Laryngeal Diseases